Investigating Students’ Perceptions on E-Learning Materials and Tools for English for MICE - Ririn Pratiwi Suharto (Universitas Tidar, 2022)
Students in vocational higher education find difficulties in joining practical courses, such as English for MICE in post-pandemic era of COVID-19. That course offers students ability to practice and held events in Meeting, Incentive Travels, Conventions, and Exhibitions. Some recent studies have examined that similar problem by using various learning method in English for MICE course. Most of them didn’t mention about the case of students’ perceptions on English for MICE course. This study offers case study that investigate students’ perceptions on e-learning materials and tools for English for MICE course. The research subjects were 20 students, in D-IV English for Tourism Industry, State Polytechnic of Malang. The results of questionnaire showed that e-learning materials and tools are the best solutions for English for MICE course. However, mostly students experienced difficulties about lacks of internet connection, but this problem obviously solved well by lecturers and students in English for MICE course. The implication of this study is that by investigating students’ perceptions on that problem, it can minimize the challenges in teaching English for MICE in post-pandemic era of COVID-19.